(untitled) (Journal of Dhaka National Medical College & Hospital, 2017)
Background: The right choice of anti-diabetic drugs among type 2 diabetic patients carries a vital role. Objective: The aim of the present study was to evaluate the prescribing patterns of anti-diabetic drugs among type 2 diabetic patients at tertiary level teaching hospital in Mymensingh. Methods: A descriptive, cross sectional study was conducted from July 2015 to June 2016 among patients attending at Medicine Outpatient Department of the Community Based Medical College Hospital. Data were collected through the reviewing of the prescriptions and interviewing of the patients. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to know the prescribing patterns of anti-diabetic drugs among type 2 diabetic patients. The study was approved by the institutional ethical committee. Results: In a pool of 150 type 2 diabetics, more than half were female (n=100, 67%). Higher proportion (54.7%) of diabetes was among middle aged patients (41-60 years). A total of 558 drugs were prescribed during the study period. Less than half (45.9%) of the total prescribed drugs were to the anti-diabetic groups. Sulfonylureas were the most commonly prescribed class (64.7%) followed by Biguanides (45.3%). Half of the patients (50.7%) were prescribed with two anti-diabetic drugs. Average number of drugs per prescription was 3.72. None of the drugs was prescribed by generic name. Drugs prescribed from an essential drug list (EDL) were 51.9%. Conclusion: Prescribing pattern need to be improved in accordance with World Health Organization (WHO) core prescribing indicator. This study will help the clinician to take appropriate measure for the improvement of prescribing patterns and use of essential drugs to the patients to prevent prescribing errors and thus promote rational use of drugs. J. Dhaka National Med. Coll. Hos. 2017; 23 (01): 29-32